Is conceiving a child to benefit another against the interests of the new child?. Issue 6 (27th May 2005) - Spriggs, M
Abstract : Conceiving a child by way of embryo selection and tissue matching to benefit a sick sibling is generally justified on the grounds that as well as the potential to save the sick child, there is a benefit for the new baby. The new baby is selected so he or she will not have the disease suffered by the first child. It is not possible, however, to select against conditions for which there is no test and Jamie Whitaker's birth is a case where the process of in vitro fertilisation with tissue matching is viewed as being of benefit only to a third party—the sick child. Some people object to using the technology for this purpose. There are also good reasons to argue that the technology should be used to save a sick child, and that it would be morally remiss for Jamie's parents not to consent to the use of his cord blood.